Education, Translation and Global Market Pressures Curriculum Design in China and the UK - Hu, Wan (Springer Singapore, 2018)
This book investigates the market-driven transformation of the higher education sector and the response given by the translation programmes in the UK and China, two vastly different social and economic contexts. It provides an in-depth look at six selected case studies, critically analysing how social, economic, and political factors have affect curriculum designs in different translation programmes. This innovative volume contributes to the development of knowledge in an important area of translation studies and opens a new way for providing both cross-national and cross-disciplinary perspectives in analysing the curricula of translation programmes.